The scope of the critique against the Athenian justice in Aristophanes’ Wasps (Circe de clásicos y modernos, 2018)
This paper explores the scope and limits of the critique against the judicial power in Wasps from the comparative analysis of the figure of Philocleon and the chorus of judges. Some authors have argued the hypothesis that Wasps is targeted against the democratic and judicial system as a whole. However, in our view, the complex game of identification and difference between Philocleon and the chorus ends up restricting the general scope of the satire and circumscribing it to particular abuses of bad Athenian judges, represented by the character of Philocleon.
Keywords: judicial system; satire; chorus of judges; Philocleon; differences